A rapid cosmic-ray increase in BC 3372–3371 from ancient buried tree rings in China. Issue 1 (December 2017) - Wang, F.; Yu, H.; Zou, Y.; Dai, Z.; Cheng, K.
Abstract Cosmic rays interact with the Earth's atmosphere to produce14 C, which can be absorbed by trees. Therefore, rapid increases of14 C in tree rings can be used to probe previous cosmic-ray events. By this method, three14 C rapidly increasing events have been found. Plausible causes of these events include large solar proton events, supernovae, or short gamma-ray bursts. However, due to the lack of measurements of14 C by year, the occurrence frequency of such14 C rapidly increasing events is poorly known. In addition, rapid increases may be hidden in the IntCal13 data with five-year resolution. Here we report the result of14 C measurements using an ancient buried tree during the period betweenbc 3388 and 3358. We found a rapid increase of about 9‰ in the14 C content frombc 3372 tobc 3371. We suggest that this event could originate from a large solar proton event. 14 C can be absorbed by trees as a result of the interaction of cosmic rays produced by high-energy phenomena with the Earth's atmosphere. Here, the authors observe a rapid increase of14 C in an ancient buried tree from BC 3372 to BC 3371, and suggest that it could originate from a large solar proton event.